Neuroplasticity Mechanisms Underlying Tai Chi’-induced Enhancement involved in Cortical Excitability - Zhao, Xudong; Hou, Lijuan; Wang , Jun (The Journal of the International Society of Chinese Health Practices, 2025)
See PDF for details